RESPONSlVlTAS DINAS PERDAGANGAN DALAM PENYEDIAAN FASlLlTAS DIFABEL - Sudaryanti Sudaryanti; Salsabila Almas Nadhifa (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2021)
Disability still has difficulty testing the accessibility of a number of Klewer Market facilities after the revitalization. The market facility availability has not followed the applicable regulations and local rules regulating disabled equality. If the local government is responsive, then complaints from people with disabilities can be handled properly so that disabled facilities at Klewer Market can be available according to accessibility standards. This research needs to be done to find out the extent to which the government is responsive to the needs of people with disabilities. The research method used was qualitative with a descriptive approach. Data collection was performed by interviews, observations, and documentation. The study results show that the responsiveness of the Trade Office of Surakarta City in providing disability facilities at Klewer Market was analyzed using four responsiveness indicators of Agus Dwiyanto: (1) The attitude of the Trade Office in responding to complaints and suggestions from disabled people; (2) The utilization of complaints and suggestions from disabled people as references for future improvements; (3) The action of the Trade Office to administer satisfaction to disabled people; (4) Disability placement by the Trade Office in the market construction planning system.